(untitled) (Papeles, 2024)
Introduction: The picturebook, understood as a reflexive object in which text and image dialogue in a complementary way, proposes an innovative didactic in the promotion and development of children’s language skills, through the acquisition of metalinguistic and metaliterary skills, and the ability to relate and comprehend the text and the image in order to enhance their learning. Methodology: This article aims to analyze the picturebook’s role as a tool for the development of language skills in Elementary School children, to revindicate it as an educational tool with great recreational and teaching potential. This by means of a thorough literature review and a narrative analysis, whose data collection tool were semi-structured interviews with Elementary School teachers, as well as to publishers, writers, and illustrators of picturebooks. Results and Discussion: These interviews, together with the previous conceptualization of the project, led to some findings on what the implementation and development of the picture book implies. Given that the perspectives analyzed were those of the actors who intervene in it from its creation as an editorial object that emerges in the dialogue between text and image; as well as the perspectives of those who use it as a tool in the classroom, discerning the role it plays in the development of language skills of elementary school children. Conclusions: Finally, the article presents the possibilities of the picturebook as a didactic tool through the comprehension reached regarding its pedagogical, aesthetic and critical thinking training function.